2016
DOI: 10.19044/esj.2016.v12n15p394
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Video Based Simulation Training On Neonatal Examination Competency Among Turkish Nursing Students

Abstract: Purpose: The aim of this study was to determine the effect of video based simulation training on nursing student's competency of neonatal examination (NE) skill. Method: An experimental, randomized controlled design was used. This study conducted with 46 junior nursing students in Ankara, Turkey. Results: Average of the achievement test of experimental group after the video based simulation training was 13.48±1.44 and the mean score of OSCE was 18.43±2.46. The mean score of control group achievement test was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
9
0
3
Order By: Relevance
“…Sonuçta da öğrencilerin alana yönelik yeterliklerini değerlendirmek için OSCE formu kullanıldığı belirtilmiştir. Çalışmada hemşirelik eğitiminde simülatör kullanımı öğrencilerin yenidoğan konusundaki beceri yeterliklerine olumlu ve önemli bir katkı sunduğu görülmüştür (Pınar et al, 2016) Similatörlerin kullanıldığı diğer bir çalışmada ise hastanede yatan riskli durumdaki hastayı tanımak ve durumu yönetmekte simülasyonun etkisine değerlendirilen çalışmadır. Çalışmada, eğitim verilen grupların özyeterliklerinin ve OSCE ile alana yönelik yeterliklerinin değerlendirildiği görülmektedir.…”
Section: Simülatör Kullanımıunclassified
See 2 more Smart Citations
“…Sonuçta da öğrencilerin alana yönelik yeterliklerini değerlendirmek için OSCE formu kullanıldığı belirtilmiştir. Çalışmada hemşirelik eğitiminde simülatör kullanımı öğrencilerin yenidoğan konusundaki beceri yeterliklerine olumlu ve önemli bir katkı sunduğu görülmüştür (Pınar et al, 2016) Similatörlerin kullanıldığı diğer bir çalışmada ise hastanede yatan riskli durumdaki hastayı tanımak ve durumu yönetmekte simülasyonun etkisine değerlendirilen çalışmadır. Çalışmada, eğitim verilen grupların özyeterliklerinin ve OSCE ile alana yönelik yeterliklerinin değerlendirildiği görülmektedir.…”
Section: Simülatör Kullanımıunclassified
“…Kişinin kendini yeterli hissetmesi durumu; bireyin öğrenme hızı, görev almaya istekliliği, güçlüklerle baş etme yeteneği ve psikolojik sağlamlığı, iletişimdeki başarısı, motivasyonu, stres ve kaygı durumu, problem çözme ve eleştirel düşünme yeteneği gibi pek çok yönünün gelişmesine katkı sunmaktadır. Bunların tamamı kişinin toplum içinde var olduğu yeri belirleyen önemli özelliklerdir (Pınar et al, 2016;Stayt et al, 2015;Zartman et al, 2002).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…15 Video simulation has several benefits including: being more practical and cost-efficient, and have higher impact in learning particularly in communication and technical skills. 13,14,16 In addition, Dyer et al found from their study state that video simulation is effective to be implemented in low resource settings. 17 Yet, today there is still lacked studies investigating the efficacy of using video simulations in education in low resource settings such as in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan the education of nursing students is mostly based on the traditional methods that are lacking the component of adequate learning and training in neonatal resuscitation 11,12 , resulting in an insufficient knowledge among many trainees on assessment 12 . Though, in recent decades the neonatal resuscitation program (NRP) has been adapted both in developing and developed countries.…”
Section: Introductionmentioning
confidence: 99%